2021
DOI: 10.1111/jgs.17041
|View full text |Cite
|
Sign up to set email alerts
|

Medication review interventions to reduce hospital readmissions in older people

Abstract: Objective: To assess the efficacy of medication review as an isolated intervention and with several co-interventions for preventing hospital readmissions in older adults. Methods: Ovid MEDLINE, Embase, The Cochrane Central Register of Controlled Trials and CINAHL were searched for randomized controlled trials evaluating the effectiveness of medication review interventions with or without co-interventions to prevent hospital readmissions in hospitalized or recently discharged adults aged ≥65, until September 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…A recent systematic review highlights the paucity of research into the impact of optimizing prescriptions on clinical outcomes in older people living with frailty [ 55 ]. However, there is some evidence that MR can reduce the number of hospital readmissions among older people [ 56 ] and can prevent the decline of mental health, with no significant effects on other outcome measurements, apart from a reduction in the number of prescribed medications [ 57 , 58 ]. Thus, overall it is accepted that several studies suggest that medication optimization could be safe, feasible well-tolerated, and lead to important benefits [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review highlights the paucity of research into the impact of optimizing prescriptions on clinical outcomes in older people living with frailty [ 55 ]. However, there is some evidence that MR can reduce the number of hospital readmissions among older people [ 56 ] and can prevent the decline of mental health, with no significant effects on other outcome measurements, apart from a reduction in the number of prescribed medications [ 57 , 58 ]. Thus, overall it is accepted that several studies suggest that medication optimization could be safe, feasible well-tolerated, and lead to important benefits [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medication review is a widely used strategy and with better outcomes to reduce potentially inappropriate prescribing (PIP) in hospitalized older adults. However, in a recent review, Dautzenberg et al (2021) reported that the heterogeneity between studies does not allow reaching significant conclusion. According to dos Santos et al (2019) , the choice of outcome measures, study design, and methodological quality of medication review studies make it difficult to analyze the effectiveness of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the growing use of computerized prescriptions has allowed the integration of digital prescription support tools aimed at automatically alerting prescribers when patients are at risk of interacting or inappropriate drugs. In some countries, this improvement could also be due to the spread of pharmaceutical care and medication review services [ 30 ], which in local experiences have been shown to improve prescriptive quality and clinical outcomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%